2006
DOI: 10.1086/505147
|View full text |Cite
|
Sign up to set email alerts
|

The Survival Benefits of AIDS Treatment in the United States

Abstract: At least 3.0 million years of life have been saved in the United States as a direct result of care of patients with AIDS, highlighting the significant advances made in HIV disease treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
354
2
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 518 publications
(366 citation statements)
references
References 46 publications
(81 reference statements)
2
354
2
8
Order By: Relevance
“…Valcour and Shiramizu [18] have in their work indicated that an increased level of ROS may also increase blood-brain barrier permeability and contribute to HIV-associated dementia. Access to potent antiretroviral therapy (ART) decreases morbidity and mortality due to HIV infection and AIDS [19] and has made HIV infection a manageable chronic illness. Unfortunately, many patients who are prescribed chronic ART experience drug toxicities that include metabolic, hepatic, neurological and cardiovascular complications [20].…”
Section: Introductionmentioning
confidence: 99%
“…Valcour and Shiramizu [18] have in their work indicated that an increased level of ROS may also increase blood-brain barrier permeability and contribute to HIV-associated dementia. Access to potent antiretroviral therapy (ART) decreases morbidity and mortality due to HIV infection and AIDS [19] and has made HIV infection a manageable chronic illness. Unfortunately, many patients who are prescribed chronic ART experience drug toxicities that include metabolic, hepatic, neurological and cardiovascular complications [20].…”
Section: Introductionmentioning
confidence: 99%
“…Esto se debería a que la mayor prescripción de fármacos aumenta la complejidad de la posología, aumentando a la vez la posibilidad de interacciones farmacológicas. De esta manera se hace necesario enfatizar la monitorización de los parámetros clínicos, especialmente, en pacientes con más de seis fármacos concomitantes (polifarmacia) de forma de detectar y tratar oportunamente los PRMs que se generen aumentando la efi cacia, seguridad y adherencia del TARV 22,23 .…”
Section: Discussionunclassified
“…The use of antiretroviral therapy (ART) has significantly reduced the mortality and morbidity caused by human immunodeficiency virus type-1 (HIV-1) [1]. ART aims at suppressing HIV-1 replication and enhancing immune reconstitution assessed by increased CD4 + T cell counts [2].…”
Section: Introductionmentioning
confidence: 99%